The effect of combined-antioxidant supplementation on serum IL-6, CK, CK-MM & T-AOC in athletes after exercise - Zhang, H.; Cai, W. L.; Su, Q. S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: This study aimed to observe the serum levels of IL-6, CK, CK-MM, LDH, T-AOC, SOD, GSH-Px and MDA at different times and changes in the degree of muscle soreness after a single bout of intensive centrifugal exercise and the effect of a combined-antioxidant on these measures. This research examines the mechanism by which the antioxidant may impact on the occurrence of oxidative stress and lipid peroxidative injury. This paper also discusses how this may be useful in abating delayedonset muscle soreness (DOMS) and exercise induced skeletal muscle injury.